Ophthalmia neonatorum due to Escherichia coli: A rare cause or an emerging bacterial etiology of neonatal conjunctivitis?. Issue 8 (5th August 2022) - Saadeh‐Jackson, Stephanie; Rodriguez, Linnet; Leffler, Christopher T.; Freymiller, Casey; Wolf, Elizabeth; Wijesooriya, Niran; Couser, Natario L.
Abstract: Since the introduction of universal gonococcal and chlamydia prophylaxis, other etiologies for neonatal conjunctivitis such as Escherichia coli have become more common. Early eye culturing as part of the management plan could provide swifter treatment and preservation of vision potential in affected neonates. Abstract : It is important to develop a diagnostic decision tree for ophthalmia neonatorum secondary to nontraditional bacterial causes such as Escherichia coli and to confidently identify their associated clinical presentations in order to ensure swift treatment and preservation of vision potential among neonates.